2007
DOI: 10.1111/j.1365-294x.2006.03189.x
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of diversity and community structure in marine bacterioplankton

Abstract: Because of their small size, great abundance and easy dispersal, it is often assumed that marine planktonic microorganisms have a ubiquitous distribution that prevents any structured assembly into local communities. To challenge this view, marine bacterioplankton communities from coastal waters at nine locations distributed world-wide were examined through the use of comprehensive clone libraries of 16S ribosomal RNA genes, used as operational taxonomic units (OTU). Our survey and analyses show that there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
380
10
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(445 citation statements)
references
References 70 publications
48
380
10
2
Order By: Relevance
“…inhabit these environments (Ivanikova et al, 2007;Haverkamp et al, 2008). This is consistent with the conclusions of Pommier et al (2007), who found signals of endemism within the global bacterioplankton community. Therefore, we conclude that the high phylogenetic resolution provided by the cpcBA operon is useful to assess the microdiversity of Synechococcus strains in the Baltic Sea and other semienclosed ecosystems.…”
Section: Microdiversity Recombination and Endemismsupporting
confidence: 81%
“…inhabit these environments (Ivanikova et al, 2007;Haverkamp et al, 2008). This is consistent with the conclusions of Pommier et al (2007), who found signals of endemism within the global bacterioplankton community. Therefore, we conclude that the high phylogenetic resolution provided by the cpcBA operon is useful to assess the microdiversity of Synechococcus strains in the Baltic Sea and other semienclosed ecosystems.…”
Section: Microdiversity Recombination and Endemismsupporting
confidence: 81%
“…Additionally, in a microcosm experiment where CH 4 is formed in DMSP spiked seawater, the CARD-FISH analysis shows that Archaea remained negligible in the DMSP supplemented approaches while Bacteria became nearly 100% of the community and alpha and gamma-proteobacteria together accounted for more than 75% of the DAPI-stained cells (Damm et al, 2010). Recent observations indicated that Alphaproteobacteria (including SAR11) and Rodobacteria are dominant in upwelling system off central Chile (Pommier et al, 2007;Aldunate, personal communication). The cosmopolitan distribution of Alphaproteobacteria supports the hypothesis that these bacteria are able to produce CH 4 in surface waters.…”
Section: Rates Of Methane Produced In Surface Watersmentioning
confidence: 99%
“…Darling et al 2000;Esteban et al 2007; see also Brown & Hovmøller 2002). Most studies to date suggest that neither marine nor soil bacteria show the latitudinal diversity gradient (Baldwin et al 2005;Fierer & Jackson 2006), but there are recent exceptions (Pommier et al 2007) which may be common among larger microbes (e.g. tintinnids; Dolan et al 2006;see Finlay 2002); indeed, organisms with large, but subhemispheric, ranges are expected to show strong broad peaks in latitudinal diversity under the mid-domain model, with patterns of local species richness being modified by small-scale environmental heterogeneity (Colwell et al 2004(Colwell et al , 2005. )…”
Section: Comparing Marine and Terrestrial Organisms In Physically Simmentioning
confidence: 99%